Survival of patients treated with extended-hours haemodialysis in Europe: an analysis of the ERA-EDTA Registry. Issue 3 (18th November 2019) - Jansz, Thijs T; Noordzij, Marlies; Kramer, Anneke; Laruelle, Eric; Couchoud, Cécile; Collart, Frederic; Cases, Aleix; Arici, Mustafa; Helve, Jaako; Waldum-Grevbo, Bård; Rydell, Helena; Traynor, Jamie P; et al.
Abstract: Background: Previous US studies have indicated that haemodialysis with ≥6-h sessions [extended-hours haemodialysis (EHD)] may improve patient survival. However, patient characteristics and treatment practices vary between the USA and Europe. We therefore investigated the effect of EHD three times weekly on survival compared with conventional haemodialysis (CHD) among European patients. Methods: We included patients who were treated with haemodialysis between 2010 and 2017 from eight countries providing data to the European Renal Association–European Dialysis and Transplant Association Registry. Haemodialysis session duration and frequency were recorded once every year or at every change of haemodialysis prescription and were categorized into three groups: CHD (three times weekly, 3.5–4 h/treatment), EHD (three times weekly, ≥6 h/treatment) or other. In the primary analyses we attributed death to the treatment at the time of death and in secondary analyses to EHD if ever initiated. We compared mortality risk for EHD to CHD with causal inference from marginal structural models, using Cox proportional hazards models weighted for the inverse probability of treatment and censoring and adjusted for potential confounders. Results: From a total of 142 460 patients, 1338 patients were ever treated with EHD (three times, 7.1 ± 0.8 h/week) and 89 819 patients were treated exclusively with CHD (three times, 3.9 ± 0.2 h/week). Crude mortality rates were 6.0 and 13.5/100 person-years. In the primary analyses, patients treated with EHD had an adjusted hazard ratio (HR) of 0.73 [95% confidence interval (CI) 0.62–0.85] compared with patients treated with CHD. When we attributed all deaths to EHD after initiation, the HR for EHD was comparable to the primary analyses [HR 0.80 (95% CI 0.71–0.90)]. Conclusions: EHD is associated with better survival in European patients treated with haemodialysis three times weekly.